Contact texts and legal discourse in the Andes (16th and 17th centuries) - Garatea Grau, Carlos (2012)
The aim of this article is to show the complex textual universe produced in Peru during the language contact and, in particular, in the history of the Spanish colonial. From references and examples when traveling over a complex reality, markedly heterogeneous, that reflects the diversity inherent in the language contact during the sixteenth and seventeenth centuries. At the same time, offer testimonials about the importance of legal discourse in the register of the Andean Spanish and concludes by highlighting the notable verbal capacity of Guaman Poma de Ayala.